2022
DOI: 10.3390/ijerph192315791
|View full text |Cite
|
Sign up to set email alerts
|

Social Connections and Self-Perceived Depression: An Enhanced Model for Studying Teenagers’ Mental Wellbeing

Abstract: The rising prevalence of depression among teenagers in Malaysia as well as globally makes it a vital issue to study. The purpose of this research is to examine the effects of social connection and self-perceived depression towards the improved mental wellbeing of the teenagers of Malaysia. Moreover, the mediating role of self-perceived depression on the improvement of the mental wellbeing of teenagers is examined in this study. This study followed a questionnaire-based approach. The sample of this study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…One possibility is that the group‐based format of both interventions was a crucial treatment component: because of the rare nature of NF, participants had perhaps not previously interacted with a group of people who understood and shared their condition and experience. Social connection is associated with improvements in both depression (Leskelä et al, 2006; Sarwar et al, 2022; Scardera et al, 2020) and anxiety (Hart & Hittner, 1991; Rueger et al, 2010; Scardera et al, 2020) and social support improvements have been shown to mediate the effects of psychosocial treatments even for individual therapy (Dour et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the group‐based format of both interventions was a crucial treatment component: because of the rare nature of NF, participants had perhaps not previously interacted with a group of people who understood and shared their condition and experience. Social connection is associated with improvements in both depression (Leskelä et al, 2006; Sarwar et al, 2022; Scardera et al, 2020) and anxiety (Hart & Hittner, 1991; Rueger et al, 2010; Scardera et al, 2020) and social support improvements have been shown to mediate the effects of psychosocial treatments even for individual therapy (Dour et al, 2014).…”
Section: Discussionmentioning
confidence: 99%